(untitled) (Economic and Political Thought, 2016)
The purpose of the article is to analyse foreign and military policy of Russia under Vladimir Putin and to attempt to show its premises, objectives and goals. The author tries to answer many questions about contemporary Russia, for example: if it seeks to regain the superpower status and whether its foreign policy threatens international security. Moreover, it tries to answer questions on the future of Russia and its role on the international arena as well as the future of President Vladimir Putin. The main thesis of the article is the observation that the objectives and tasks that Vladimir Putin set foreign and military policy of Russia pose a serious threat to peace in Europe and international security. The author shows here that Vladimir Putin is consistent in his full commitment to the reconstruction of economic and military power of Russia, and his main aim is to strengthen Russia’s position on the international arena, i.e. obtain the position that the Soviet Union had. However, if the policy is not based on a stable political and economic system, it may result in a catastrophe for Russia and its present leader.